which of the following is a factor of (x+y)^3 - (x^3 + y^3)?
Answers
Answered by
5
Answer:
d) Now, (x+ y)3 – (x3 + y3) = (x + y) – (x + y)(x2– xy + y2)
[using identity, a3 + b3 = (a + b)(a2 -ab+ b2)] = (x+ y)[(x+ y)2 -(x2 -xy+ y2)]
= (x+ y)(x2+ y2+ 2xy- x2+ xy- y2)
[using identity, (a + b)2 = a2 + b2 + 2 ab)]
= (x + y) (3xy)
Hence, one of the factor of given polynomial is 3xy.
Answered by
2
Answer:
3XY(X+Y)
Step-by-step explanation:
SOLN
FIND
(X+Y)^3-(X^3+Y^3)
SO ((X+Y)^3=X^3+Y^3 + 3 X^2 Y + 3 Y^2 X
(X+Y)^3-(X^3+Y^3)
x^3+y^3+3x^2y+3y^2x-x^3-y^3
answer is 3xy(x+y)
HOPE THIS WILL HELP YOU
Similar questions